2011
DOI: 10.1111/j.2042-3306.2011.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of BPV‐1 L1 virus‐like particles in a dose‐escalation vaccination trial in horses

Abstract: BPV-1 L1 VLPs constitute a promising vaccine candidate for prevention of BPV-1/-2-induced disease in equids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 39 publications
(90 reference statements)
2
29
0
5
Order By: Relevance
“…Neutralization titers were induced at levels that correlate with protection in both, experimental animals and man. 87 Induction of a protective immune response was also previously reported in cattle (reviewed in Ref. 88), rabbits (cottontail rabbit papillomavirus, CRPV) 89 and dogs (canine oral papillomavirus).…”
Section: Papillomavirusesmentioning
confidence: 78%
“…Neutralization titers were induced at levels that correlate with protection in both, experimental animals and man. 87 Induction of a protective immune response was also previously reported in cattle (reviewed in Ref. 88), rabbits (cottontail rabbit papillomavirus, CRPV) 89 and dogs (canine oral papillomavirus).…”
Section: Papillomavirusesmentioning
confidence: 78%
“…Despite a robust humoural response against L1 [60] and a tendency for tumour regression in some animals, results were not conclusive. However, very recently, BPV-1 L1 VLPs were tested in a dose-escalation trial for the vaccination of healthy horses and were shown to induce a long-lasting humoural response, which the authors deemed appropriate for protection [8].…”
Section: Prophylactic and Therapeutic Vaccinesmentioning
confidence: 99%
“…Research on BPV has led to most of the recent breakthroughs on the biology and pathology of animal papillomavirus, with major implications for human health. Using such spontaneous models, researchers have recently made significant discoveries on the interaction of papillomavirus with chemical carcinogens and immunosuppressants [4], on the role of BPV oncoproteins in cell transformation and immune evasion, on the infection of some unusual cell types and the possibility of haematogenous transplacental BPV transmission [5], as well as on new prophylactic and therapeutic vaccines [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that intramuscular vaccination of horses with bovine papillomavirus (BPV-1) L1-VLPs results in a long-lasting antibody response against the virus. Neutralization titres were induced at levels that correlate with protection in both, experimental animals and man (Hainisch et al, 2012). Induction of a protective immune response was also previously reported in cattle (reviewed in (Campo, 1997)), rabbits (cottontail rabbit papillomavirus CRPV) (Breitburd et al, 1995) and dogs (canine oral papillomavirus) (Suzich et al, 1995).…”
Section: Animal Virus Vlps As Vaccine Immunogensmentioning
confidence: 57%